2017
DOI: 10.1155/2017/1356385
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gabor Phase Based Illumination Invariant for Face Recognition

Abstract: This paper presents a novel Gabor phase based illumination invariant extraction method aiming at eliminating the effect of varying illumination on face recognition. Firstly, It normalizes varying illumination on face images, which can reduce the effect of varying illumination to some extent. Secondly, a set of 2D real Gabor wavelet with different directions is used for image transformation, and multiple Gabor coefficients are combined into one whole in considering spectrum and phase. Lastly, the illumination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It can be seen that the recognition rates of Luminance quantization were lower than that of MSB quantization by SVM with linear and RBF kernel function. That is because the MSB method produces values which better discriminate the colours [16,17]. Thus, it can better describe the colour information of different pigs.…”
Section: Results Of Pig Identification For Pigsty No2 321 Results Of Different Quantization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the recognition rates of Luminance quantization were lower than that of MSB quantization by SVM with linear and RBF kernel function. That is because the MSB method produces values which better discriminate the colours [16,17]. Thus, it can better describe the colour information of different pigs.…”
Section: Results Of Pig Identification For Pigsty No2 321 Results Of Different Quantization Methodsmentioning
confidence: 99%
“…However, pigs may move to different positions in a real pigsty with complex illumination. Therefore, Gabor phase response is also calculated in the proposed method because its insensitivity to illumination conditions [16,17]. The main difference of Gabor phase response on the vth scale is encoded by the same way, which is described as MLDDN_Pv(x, y).…”
Section: Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaur et al proposed a method that extracts LOG-DCT features from retinex images [11]. Fan et al proposed a method based on the phase of 2D Gabor features [12]. Zhu et al proposed using logarithm gradient orientation and logarithm gradient magnitude to derive gradient histogram [13].…”
Section: Journal Of Computer Sciences and Applicationsmentioning
confidence: 99%
“…For example, a variety of subspace-based methods have been proposed [3,4]. Methods based on illumination-invariant features have also been proposed [5][6][7][8][9][10][11][12][13][14]. On the other hand, previous studies have shown that spectral information is useful for this purpose [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%